ANALISA DAMPAK KEBIJAKAN PEMERINTAH TENTANG COVID-19 TERHADAP PRASARANA, SARANA DAN SDM PERKERETAAPIAN YANG BERPENGARUH PADA KUALITAS LAYANAN PT MRT JAKARTA TAHUN 2021 - Handri Pirmansah; Julison Arifin; Erman Noor Adi; Masjraul Hidayat; Soemino Eko Saputro (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
In 2020, a pandemic hit Indonesia, resulting in many Indonesians being exposed to the Covid-19 virus. To reduce and reduce the risk of Covid-19 transmission, the government has imposed a restrictive policy known as the Enforcement of Community Activity Restrictions (PPKM) in all areas of the islands of Java and Bali. The impact of the implementation of this policy is the reduction in the number of passengers per day on all transportation lines. The purpose of this study was to determine the effect of government policies on railway infrastructure, facilities and human resources as well as MRT Jakarta operations which affect the service quality of PT MRT Jakarta. The method used is quantitative by distributing questionnaires to passengers using MRT Jakarta. The results of the study are government policies have a significant influence on infrastructure, facilities, human resources and MRT Jakarta train operations and train operations have a significant influence on PT MRT Jakarta's service quality as much as 84.8%.